Mitochondria-ER contact sites expand during mitosis - Fang Yu (156838) (2024)
Mitochondria-ER contact sites (MERCS) are involved in energy homeostasis, redox and Ca2+ signaling, and inflammation. MERCS are heavily studied; however, little is known about their regulation during mitosis. Here, we show that MERCS expand during mitosis in three cell types using various approaches, including transmission electron microscopy, serial EM coupled to 3D reconstruction, and a split GFP MERCS marker. We further show enhanced Ca2+ transfer between the ER and mitochondria using either direct Ca2+ measurements or by quantifying the activity of Ca2+-dependent mitochondrial dehydrogenases. Collectively, our results support a lengthening of MERCS in mitosis that is associated with improved Ca2+ coupling between the two organelles. This augmented Ca2+ coupling could be important to support the increased energy needs of the cell during mitosis. Other Information Published in: iScience License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.isci.2024.109379